Skywatch: Enhancing Military Camp Surveillance With PC-Based Monitoring using Drone Camera Technology at Fort Bonifacio - Q. de Leon, Jonathan; T. Caliliw, Maricar; C. Ambag, Silvia (LPPM Universitas Duta Bangsa Surakarta, 2024)
Drones, or Unmanned Aerial Vehicles (UAVs), are widely used in various applications, most notably military surveillance. This abstract describes a PC-based drone system designed specifically for surveillance in camp areas. The system incorporates advanced features such as real-time video streaming and autonomous flight capabilities to improve security and situational awareness in military environments. The drone, a hexacopter equipped with high-resolution cameras, captures live video transmitted to a ground control station (GCS) running on a PC for immediate monitoring and analysis. This allows troops in charge of camp security to quickly access critical information. The PC-based drone's standout feature is its autonomous flight capability, enabling it to follow predetermined routes using GPS and navigation devices, or it can be remotely controlled via the PC-based ground station. The research demonstrated the drone's effectiveness in detecting and tracking objects, including vehicles and people, thereby enhancing security measures at military camps. However, limitations such as range, battery life, and potential interference were noted. Further research is necessary to optimize the system for specific surveillance scenarios. Overall, the study underscores the potential of PC-based drones for military surveillance and lays the groundwork for future advancements.